Carotid blowout syndrome in patients treated by larynx cancer - Estomba,Carlos Miguel Chiesa (2017)
Abstract Introduction: Carotid blowout syndrome is an uncommon complication for patient treated by head and neck tumors, and related to a high mortality rate. Objective: The aim of this study was to study the risk of carotid blowout in a large cohort of patients treated only by larynx cancer. Methods: Retrospective analysis of patients older than 18 years, treated by larynx cancer who developed a carotid blowout syndrome in a tertiary academic centre. Results: 197 patients met the inclusion criteria, 192 (98.4%) were male and 5 (1.6%) were female. 6 (3%) patients developed a carotid blowout syndrome, 4 patients had a carotid blowout syndrome located in the internal carotid artery and 2 in the common carotid artery. According to the type of rupture, 3 patients suffer a type I, 2 patients a type III and 1 patient a type II. Five of those patients had previously undergone radiotherapy and all patients underwent total laryngectomy. We found a statistical correlation between open surgical procedures (p = 0.004) and radiotherapy (p = 0.023) and the development of a carotid blowout syndrome. Conclusion: Carotid blowout syndrome is an uncommon complication in patients treated by larynx tumours. According to our results, patient underwent radiotherapy and patients treated with open surgical procedures with pharyngeal opening have a major risk to develop this kind of complication.